ANALISIS PASAR DAN STRATEGI PENJUALAN BAWANG MERAH DI PEDURUNGAN ASRI - fortuna, givan; Agus Arwani; Ina Mutmainah (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2024)
This research discusses market analysis and sales strategies for shallots in certain locations, with the aim of understanding local market dynamics and designing effective sales strategies. The analytical approach includes identifying market profiles, consumer behavior, and related trade policies that influence the onion industry in the region. Data from field surveys, interviews with stakeholders, and literature searches form the basis for a comprehensive analysis. The results of the market analysis highlight the high demand for shallots in this region, driven by consumer preferences for traditional dishes that rely on shallots as a staple ingredient. Recommended sales strategies include optimizing the supply chain, improving product quality, and utilizing technology to increase distribution efficiency. Digital marketing was identified as an effective means of increasing product visibility, by leveraging online platforms and social networks. Partnerships with local merchants and restaurants are described as a collaborative strategy that can expand market reach and build consumer trust. It is important to note that the success of this sales strategy requires coordination between manufacturers, distributors, and retailers, as well as a deep understanding of local market dynamics and the level of quality desired by consumers. This study hopes to provide guidance for shallot industry players in increasing market penetration and maximizing sales potential in this location.